Alcohol service provision for older people in an area experiencing high alcohol use and health inequalities. (March 2016) - McCabe, Karen E; Ling, Jonathan; Wilson, Graeme B; Crosland, Ann; Kaner, Eileen FS; Haighton, Catherine A
Background: UK society is ageing. Older people who drink alcohol, drink more than those from previous generations, drink more frequently than other age groups and are more likely to drink at home and alone. Alcohol problems in later life however are often under-detected and under-reported meaning older people experiencing alcohol problems have high levels of unmet need. Methods: This study sought to identify existing services within South of Tyne, North East England to capture the extent of service provision for older drinkers and identify any gaps. The Age UK definition of 'older people' (aged 50 and over) was used. Services were contacted by telephone, managers or their deputy took part in semi-structured interviews. Findings: Forty six service providers were identified. Only one provided a specific intervention for older drinkers. Others typically provided services for age 18+. Among providers, there was no definitive definition of an older person. Data collection procedures within many organisations did not enable them to confirm whether older people were accessing services. Where alcohol was used alongside other drugs, alcohol use could remain unrecorded. Conclusion: To enable alcohol services to meet the needs of older people, greater understanding is needed of the patterns of drinking in later life, the experiences of older people, the scale and scope of the issue and guidance as to the most appropriate action to take. An awareness of the issues related to alcohol use in later life also needs to be integrated into commissioning of other services that impact upon older people.